Surgical Outcomes for Upper Lumbar Disc Herniations: A Systematic Review and Meta-analysis. Issue 5 (June 2021) - Echt, Murray; Holland, Ryan; Mowrey, Wenzhu; Cezayirli, Phillip; De la Garza Ramos, Rafael; Hamad, Mousa; Gelfand, Yaroslav; Longo, Michael; Kinon, Merritt D.; Yanamadala, Vijay; Chaudhary, Saad; Cho, Samuel K.; et al.
Study Design: Systematic review and meta-analysis. Objective: To conduct a literature review on outcomes of discectomy for upper lumbar disc herniations (ULDH), estimate pooled rates of satisfactory outcomes, compare open laminectomy/microdiscectomy (OLM) versus minimally invasive surgical (MIS) techniques, and compare results of disc herniations at L1-3 versus L3-4. Methods: A systematic review of articles reporting outcomes of nonfusion surgical treatment of L1-2, L2-3, and/or L3-4 disc herniations was performed. The inclusion and exclusion of studies was performed according to the latest version of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: A total of 20 articles were included in the quantitative meta-analysis. Pooled proportion of satisfactory outcome (95% CI) was 0.77 (0.70, 0.83) for MIS and 0.82 (0.78, 0.84) for OLM. There was no significant improvement with MIS techniques compared with standard OLM, odds ratio (OR) = 0.86, 95% CI (0.42, 1.74), P = .66. Separating results by levels revealed a trend of higher satisfaction with L3-4 versus L1-3 with OLM surgery, OR = 0.46, 95% CI (0.19, 1.12), P = .08. Conclusion: Our analysis reveals that discectomy for ULDH has an overall success rate of approximately 80% and has not improved with MIS. Discectomy for herniations at L3-4 trends toward better outcomes compared with L1-2 and L2-3, but was not significant.